Answer
a) \( f(x) = -\frac{3}{2} x^{2} \):
- Inverse: \( f^{-1}(y) = -\frac{\sqrt{-6y}}{3} \)
- Graph: Downward parabola, its inverse is the left half of an upward parabola, and the line \( y=x \) is a diagonal line.
- Domain and Range: Both \( f(x) \) and \( f^{-1}(y) \) have domains and ranges of \( (-\infty, 0] \).
b) \( g(x) = -\frac{3}{2} x \):
- Inverse: \( g^{-1}(y) = -\frac{2}{3} y \)
- Graph: Straight lines with negative slopes, and the line \( y=x \) is a diagonal line.
- Domain and Range: Both \( g(x) \) and \( g^{-1}(y) \) have domains and ranges of \( (-\infty, \infty) \).
c) \( h(x) = 3x \):
- Inverse: \( h^{-1}(y) = \frac{y}{3} \)
- Graph: Straight lines with positive slopes, and the line \( y=x \) is a diagonal line.
- Domain and Range: Both \( h(x) \) and \( h^{-1}(y) \) have domains and ranges of \( (-\infty, \infty) \).
d) \( p(x) = 3x^{2} \):
- Inverse: \( p^{-1}(y) = \frac{\sqrt{3y}}{3} \)
- Graph: Upward parabola, its inverse is the right half of an upward parabola, and the line \( y=x \) is a diagonal line.
- Domain and Range: Both \( p(x) \) and \( p^{-1}(y) \) have domains and ranges of \( [0, \infty) \).
Solution
Rewrite the equation by following steps:
- step0: Rewrite in standard form:
\(y=3x\)
- step1: Move the variable to the left side:
\(y-3x=0\)
- step2: Multiply both sides:
\(-y+3x=0\)
- step3: Reorder the terms:
\(3x-y=0\)
Rewrite the equation \( y=-\frac{3}{2}x \).
Rewrite the equation by following steps:
- step0: Rewrite in standard form:
\(y=-\frac{3}{2}x\)
- step1: Multiply both sides of the equation by LCD:
\(2y=-3x\)
- step2: Move the variable to the left side:
\(2y+3x=0\)
- step3: Reorder the terms:
\(3x+2y=0\)
Solve the equation \( y=3x \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(y=3x\)
- step1: Swap the sides:
\(3x=y\)
- step2: Divide both sides:
\(\frac{3x}{3}=\frac{y}{3}\)
- step3: Divide the numbers:
\(x=\frac{y}{3}\)
Solve the equation \( y=-\frac{3}{2}x \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(y=-\frac{3}{2}x\)
- step1: Swap the sides:
\(-\frac{3}{2}x=y\)
- step2: Change the signs:
\(\frac{3}{2}x=-y\)
- step3: Multiply by the reciprocal:
\(\frac{3}{2}x\times \frac{2}{3}=-y\times \frac{2}{3}\)
- step4: Multiply:
\(x=-\frac{2}{3}y\)
Solve the equation \( y=3x^{2} \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(y=3x^{2}\)
- step1: Swap the sides:
\(3x^{2}=y\)
- step2: Divide both sides:
\(\frac{3x^{2}}{3}=\frac{y}{3}\)
- step3: Divide the numbers:
\(x^{2}=\frac{y}{3}\)
- step4: Simplify the expression:
\(x=\pm \sqrt{\frac{y}{3}}\)
- step5: Simplify:
\(x=\pm \frac{\sqrt{3y}}{3}\)
- step6: Separate into possible cases:
\(\begin{align}&x=\frac{\sqrt{3y}}{3}\\&x=-\frac{\sqrt{3y}}{3}\end{align}\)
Solve the equation \( y=-\frac{3}{2}x^{2} \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(y=-\frac{3}{2}x^{2}\)
- step1: Swap the sides:
\(-\frac{3}{2}x^{2}=y\)
- step2: Change the signs:
\(\frac{3}{2}x^{2}=-y\)
- step3: Multiply by the reciprocal:
\(\frac{3}{2}x^{2}\times \frac{2}{3}=-y\times \frac{2}{3}\)
- step4: Multiply:
\(x^{2}=-\frac{2}{3}y\)
- step5: Simplify the expression:
\(x=\pm \sqrt{-\frac{2}{3}y}\)
- step6: Simplify:
\(x=\pm \frac{\sqrt{-6y}}{3}\)
- step7: Separate into possible cases:
\(\begin{align}&x=\frac{\sqrt{-6y}}{3}\\&x=-\frac{\sqrt{-6y}}{3}\end{align}\)
Let's analyze each function step by step to determine the inverse, graph the relations, and identify the domain and range.
### a) \( f(x) = -\frac{3}{2} x^{2} \)
**i) Determine the equation of the inverse:**
To find the inverse, we set \( y = -\frac{3}{2} x^{2} \) and solve for \( x \):
\[
y = -\frac{3}{2} x^{2} \implies x = \pm \frac{\sqrt{-6y}}{3}
\]
Since \( f(x) \) is a downward-opening parabola, we restrict the domain to \( x \leq 0 \) to ensure the inverse is a function:
\[
f^{-1}(y) = -\frac{\sqrt{-6y}}{3}
\]
**ii) Graph the relation, its inverse, and the line \( y=x \):**
- The graph of \( f(x) \) is a downward parabola.
- The inverse \( f^{-1}(y) \) is the left half of the upward parabola.
- The line \( y=x \) is a diagonal line through the origin.
**iii) Domain and Range:**
- Domain of \( f(x) \): \( (-\infty, 0] \)
- Range of \( f(x) \): \( (-\infty, 0] \)
- Domain of \( f^{-1}(y) \): \( (-\infty, 0] \)
- Range of \( f^{-1}(y) \): \( (-\infty, 0] \)
---
### b) \( g(x) = -\frac{3}{2} x \)
**i) Determine the equation of the inverse:**
To find the inverse, we set \( y = -\frac{3}{2} x \) and solve for \( x \):
\[
y = -\frac{3}{2} x \implies x = -\frac{2}{3} y
\]
Thus, the inverse is:
\[
g^{-1}(y) = -\frac{2}{3} y
\]
**ii) Graph the relation, its inverse, and the line \( y=x \):**
- The graph of \( g(x) \) is a straight line with a negative slope.
- The inverse \( g^{-1}(y) \) is also a straight line with a negative slope.
- The line \( y=x \) is a diagonal line through the origin.
**iii) Domain and Range:**
- Domain of \( g(x) \): \( (-\infty, \infty) \)
- Range of \( g(x) \): \( (-\infty, \infty) \)
- Domain of \( g^{-1}(y) \): \( (-\infty, \infty) \)
- Range of \( g^{-1}(y) \): \( (-\infty, \infty) \)
---
### c) \( h(x) = 3x \)
**i) Determine the equation of the inverse:**
To find the inverse, we set \( y = 3x \) and solve for \( x \):
\[
y = 3x \implies x = \frac{y}{3}
\]
Thus, the inverse is:
\[
h^{-1}(y) = \frac{y}{3}
\]
**ii) Graph the relation, its inverse, and the line \( y=x \):**
- The graph of \( h(x) \) is a straight line with a positive slope.
- The inverse \( h^{-1}(y) \) is also a straight line with a positive slope.
- The line \( y=x \) is a diagonal line through the origin.
**iii) Domain and Range:**
- Domain of \( h(x) \): \( (-\infty, \infty) \)
- Range of \( h(x) \): \( (-\infty, \infty) \)
- Domain of \( h^{-1}(y) \): \( (-\infty, \infty) \)
- Range of \( h^{-1}(y) \): \( (-\infty, \infty) \)
---
### d) \( p(x) = 3x^{2} \)
**i) Determine the equation of the inverse:**
To find the inverse, we set \( y = 3x^{2} \) and solve for \( x \):
\[
y = 3x^{2} \implies x = \pm \frac{\sqrt{3y}}{3}
\]
Since \( p(x) \) is an upward-opening parabola, we restrict the domain to \( x \geq 0 \) to ensure the inverse is a function:
\[
p^{-1}(y) = \frac{\sqrt{3y}}{3}
\]
**ii) Graph the relation, its inverse, and the line \( y=x \):**
- The graph of \( p(x) \) is an upward parabola.
- The inverse \( p^{-1}(y) \) is the right half of the upward parabola.
- The line \( y=x \) is a diagonal line through the origin.
**iii) Domain and Range:**
- Domain of \( p(x) \): \( [0, \infty) \)
- Range of \( p(x) \): \( [0, \infty) \)
- Domain of \( p^{-1}(y) \): \( [0, \infty) \)
- Range of \( p^{-1}(y) \): \( [0, \infty) \)
---
This concludes the analysis of the functions and their inverses. If you need any further assistance or visualizations, please let me know!
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution